2019
DOI: 10.3390/en12203958
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Heat Transfer to Supercritical Water in Vertical Tube under Semicircular Heating Condition

Abstract: In-depth understanding and analysis of turbulent convection heat transfer of supercritical water under semicircular heating conditions play a major role in system design and security. The inaccurate numerical results on simulating the buoyancy effect under deterioration heat transfer cases are partly attributed to the invalidity of the turbulent model. An improved turbulence model, which is validated suitable to three-dimensional model, is adopted in the present paper to numerical simulated flow and heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…where u i u j and u i T are the turbulent stress tensor and turbulent heat flux vector, respectively [11].…”
Section: Numerical Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…where u i u j and u i T are the turbulent stress tensor and turbulent heat flux vector, respectively [11].…”
Section: Numerical Model and Methodologymentioning
confidence: 99%
“…Over the past few decades, a considerable amount of efforts have been made to investigate the heat transfer behaviors of different supercritical fluids [10]. Wang et al [11] performed The detailed temperature distributions inside the test tube were numerically visualized and are displayed in Figure 8, for two cases with different values of heat flux at p = 3.8 MPa and G = 385 kg/m 2 •s. As indicated in the figure, in both cases, the N 2 temperature increased from less than pc to more than T pc , while the location of T pc moved from the tube wall and the tube centreline along a parabolic curve in the flow direction.…”
Section: Analysis Of Heat Transfer Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research works, mainly performed numerically, have been published on this phenomenon, known as heat transfer deterioration (HTD) [41][42][43][44][45][46][47]. Recently, Wang et al [48] obtained, by simulation, that semicircular heating decreased the degree of HTD due to the greater turbulence produced by the greater density difference between the heating side and the adiabatic side.…”
Section: Heat Transfer Deterioration In Scwg Experimentsmentioning
confidence: 99%
“…The heat transfer characteristics of supercritical fluid have been investigated extensively, especially the investigation of in tubes have become a focal point of research content [8][9][10][11]. Considering the influence of different factors on heat transfer, Wang et al [12] found that the buoyancy effect under the non-uniform heat source can effectively alleviate the degree of Heat Transfer Deterioration (HTD). Meanwhile, a modified turbulent model, which can accurately predict the influence of semicircular heating condition on the flow and heat transfer, was also proposed.…”
Section: Introductionmentioning
confidence: 99%